John Ayotunde Isola Bewaji. The Rule of Law and Governance in Indigenous Yoruba Society: A Study in African Philosophy of Law. Lexington Books, 2016, 282 pages - Segun Gbadegesin (Yoruba Studies Review, 2021)
Review of John Ayotunde Isola Bewaji's The Rule of Law and Governance in Indigenous Yoruba Society: A Study in African Philosophy of Law. Lexington Books, 2016, 282 pages.